2003
DOI: 10.1073/pnas.1231043100
|View full text |Cite
|
Sign up to set email alerts
|

Decorin-binding proteins A and B confer distinct mammalian cell type-specific attachment by Borrelia burgdorferi , the Lyme disease spirochete

Abstract: Host cell binding is an essential step in colonization by many bacterial pathogens, and the Lyme disease agent, Borrelia burgdorferi, which colonizes multiple tissues, is capable of attachment to diverse cell types. Glycosaminoglycans (GAGs) are ubiquitously expressed on mammalian cells and are recognized by multiple B. burgdorferi surface proteins. We previously showed that B. burgdorferi strains differ in the particular spectrum of GAGs that they recognize, leading to differences in the cultured mammalian ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
150
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 110 publications
(157 citation statements)
references
References 59 publications
5
150
0
2
Order By: Relevance
“…Nevertheless, the present study demonstrates that B. burgdorferi-specific antibodies against selected B. burgdorferi antigens may sometimes be on May 9, 2018 by guest http://jcm.asm.org/ present in the CNS. BBA25, the most commonly recognized antigen in this study, plays an important role in spirochete pathogenesis (11,12) and has recently been shown to mediate the adherence of spirochetes to glial cells (10). Moreover, a recent report has demonstrated that BBA25 antibodies are prominent in European cases of neuroborreliosis (14).…”
mentioning
confidence: 62%
See 2 more Smart Citations
“…Nevertheless, the present study demonstrates that B. burgdorferi-specific antibodies against selected B. burgdorferi antigens may sometimes be on May 9, 2018 by guest http://jcm.asm.org/ present in the CNS. BBA25, the most commonly recognized antigen in this study, plays an important role in spirochete pathogenesis (11,12) and has recently been shown to mediate the adherence of spirochetes to glial cells (10). Moreover, a recent report has demonstrated that BBA25 antibodies are prominent in European cases of neuroborreliosis (14).…”
mentioning
confidence: 62%
“…1A). This is particularly interesting since BBA25 has recently been shown to facilitate the attachment of spirochetes to glial cells, suggesting a role in CNS pathogenesis (10). IgG against BBA23 and BBA24 was not detected in the CSF of patients with neurologic Lyme disease (Fig.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…The BBK32 protein was first identified as a B. burgdorferi surface lipoprotein that promotes bacterial binding to Fn (21) and was more recently shown to also promote binding of the high-passage-number, nonadhesive B. burgdorferi strain B314 to the GAGs heparin and dermatan sulfate (5). Several other B. burgdorferi surface proteins, including DbpA, DbpB, and Bgp, have been shown to bind GAGs, and the expression of DbpA or DbpB is sufficient to confer GAG binding by strain B314 (6,20). To assess the relative importance of BBK32 in GAG binding by strain B31 A3, we inserted a Kan cassette (conferring Kan r ) at the 5Ј end of BBK32, resulting in the B31 A3 BBK32::Kan r mutant, which was found to retain all of the endogenous plasmids of B31 A3 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, many of the discoveries on the roles of different virulence factors during mammalian and tick infection were initially made using N40, genetic stability of the culture was reported in this strain when recovered from chronically infected immunocompetent mice (78), and, in particular, immunological responses to B. burgdorferi have also been thoroughly investigated using this strain. We have been studying N40 clone D10/E9 and have examined the roles of several virulence factors in this clone (32,39,56,72,75,76,86). However, we recently began to suspect that published work from various laboratories using the strain name "N40" may in reality refer to several different strains or at least different clones of the same strain.…”
mentioning
confidence: 99%